Akuntabilitas Publik dalam Penyusunan Laporan Penyelenggaraan Pemerintah Daerah (LPPD) di Kabupaten Ponorogo - Farhana Khoirunnisa’ Hidayah; Muhammad Farid Ma'ruf; Galih Wahyu Pradana; Melda Fadiyah Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public accountability is a key principle in the implementation of good governance, particularly in fulfilling the responsibilities of local governments. One instrument of this accountability is the Regional Government Administration Report (Laporan Penyelenggaraan Pemerintahan Daerah / LPPD), which is prepared annually by regional heads and submitted to the central government. This study aims to analyze public accountability in the preparation of the LPPD in Ponorogo Regency. The research employs a descriptive qualitative approach using interviews, observations, and documentation for data collection. Informants include the LPPD preparation team at the Regional Secretariat of Ponorogo Regency and Regional Apparatus Organizations (OPD) involved in providing data. The analysis uses accountability indicators including responsiveness, debate forums, coordination, autonomy, clarity of performance evaluation standards, negotiation, accountability campaigns, evaluation and feedback, and participation and responsiveness to environmental changes. The results indicate that the preparation of the LPPD in Ponorogo Regency has followed administrative procedures and is supported by the involvement of regional agencies and a digital-based reporting system. However, its implementation remains less than optimal, particularly in terms of responsiveness of regional agencies, cross-sector coordination, public accountability campaigns, and mechanisms for public participation.